2017
DOI: 10.1016/j.aca.2017.05.037
|View full text |Cite
|
Sign up to set email alerts
|

Novel volumetric method for highly repeatable injection in microchip electrophoresis

Abstract: A novel injector for microchip electrophoresis (MCE) has been designed and evaluated that achieves very high repeatability of injection volume suitable for quantitative analysis. It eliminates the injection biases in electrokinetic injection and the dependence on pressure and sample properties in hydrodynamic injection. The microfluidic injector, made of poly(dimethylsiloxane) (PDMS), operates similarly to an HPLC injection valve. It contains a channel segment (chamber) with a well-defined volume that serves a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 66 publications
0
15
0
Order By: Relevance
“…In HPLC, the amount of sample is measured volumetrically (by the injection loop), resulting in very high injection repeatability. Recently, we explored a novel volumetric injection technique for MCE and showed that a peak area RSD as low as 1.04% (n=4) [37] could be achieved, even using an external capillary for separation. We are thus confident that a next-generation device incorporating a PDMS-based injector will achieve sufficient repeatability for radiopharmaceutical analysis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In HPLC, the amount of sample is measured volumetrically (by the injection loop), resulting in very high injection repeatability. Recently, we explored a novel volumetric injection technique for MCE and showed that a peak area RSD as low as 1.04% (n=4) [37] could be achieved, even using an external capillary for separation. We are thus confident that a next-generation device incorporating a PDMS-based injector will achieve sufficient repeatability for radiopharmaceutical analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The dead-volume could be reduced by various approaches such as precise drilling [51] or molding the capillary port [52], or by tapering the capillary to fit directly in an in-plane microchannel [37, 53]. The geometry issue could also be addressed by integration of the separation channel directly into the chip (instead of using a capillary); this would eliminate the junctions altogether and simplify the overall setup, enabling a single integrated microfluidic device for injection, separation, and detection.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…By replacing conventional HPLC methods with microchip electrophoresis (MCE), there is much potential to significantly reduce the size, cost, and complexity of chemical purity testing systems in the future. Furthermore, sample volume is generally reduced by orders of magnitude, and very short analysis times (seconds) have been reported [ 68 , 74 , 75 ].…”
Section: Miniaturization Of Quality Control Testsmentioning
confidence: 99%